Spatially explicit model of deforestation in Bolivia - Vanclay, J.K.; Kaimowitz, D.; Puntodewo, A.; Méndez, P. (1999)
A GIS compiled by the Departmental Government of Santa Cruz, Bolivia offers data that may help to resolve some competing theories of tropical deforestation. The GIS contains many attributes relating to land use at two points in time, 1989 and 1994, and allow us to address questions like: What has been the impact of past road construction on deforestation and land use? What impacts might be expected from future road construction? What impact do zoning policies such as forest concessions and protected areas have? What influence do cultural factors have on forest clearing and fragmentation? We discuss our methodology and report interim results. We seek to provoke discussion on appropriate statistical procedures for such analyses.